2009
DOI: 10.1159/000258552
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Efficiency Improvement after Slow Continuous Ultrafiltration Is Assessed by Beat-to-Beat Minimally Invasive Monitoring in Congestive Heart Failure Patients: A Preliminary Report

Abstract: Background: We have evaluate the effect of slow continuous ultrafiltration (SCUF) on cardiac output (CO) and other hemodynamic parameters related to the overall performance of the cardiovascular system in patients with congestive heart failure (CHF). Minimally invasive hemodynamic monitoring was performed via the radial artery using a pressure recording analytical method (PRAM) during SCUF treatment. Patients and Methods: Using PRAM, hemodynamic changes were assessed in 15 CHF patients (New York Heart Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 61 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…In CHF patients, ultrafiltration improves not only CO, as previously reported, but also contractile cardiac efficiency and performance [26].…”
Section: Minimally Invasive Hemodynamic Monitoringsupporting
confidence: 82%
“…In CHF patients, ultrafiltration improves not only CO, as previously reported, but also contractile cardiac efficiency and performance [26].…”
Section: Minimally Invasive Hemodynamic Monitoringsupporting
confidence: 82%
“…Numerous studies demonstrated a close association between BNP or NT-pro BNP levels and LV mass, systolic function, and fluid status in the ESRD population [15,16,17,18], but only very few studies examined the diagnostic and prognostic potential of BNP or NT-pro BNP for HF-PEF in patients on chronic maintenance HD [3,19]. …”
Section: Discussionmentioning
confidence: 99%
“…The intravascular volume reduction through use of diuretics does not often portend these benefits and even tends to produce opposite effects such as activation of renin-angiotensin-aldosterone system and sympathetic nervous system (21,22). The beneficial effects of UF on contractile cardiac efficiency and performance without an adverse effect on heart rate or BP were also reported by other investigators (23). In a recent randomized controlled study on patients with ADHF using a minimally invasive cardiocirculatory monitoring system, UF resulted in substantial increase in several parameters such as cardiac index and cardiac power output while simultaneously reducing systemic vascular resistance; these effects were not observed in the diuretic group (22).…”
Section: Neurohormonal Axismentioning
confidence: 76%